Topology of a G-quadruplex DNA formed by C9orf72 hexanucleotide repeats associated with ALS and FTD - Zhou, Bo (Sci Rep, 2015)
Abnormal expansions of an intronic hexanucleotide GGGGCC (G4C2) repeat of the C9orf72 gene are the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Previous studies suggested that the C9orf72 hexanucleotide repeat expansion (HRE), either as DNA or the transcribed RNA, can fold into G-quadruplexes with distinct structures. These structural polymorphisms lead to abortive transcripts and contribute to the pathogenesis of ALS and FTD. Using circular dichroism (CD) and nuclear magnetic resonance (NMR) spectroscopy, we analyzed the structures of C9orf72 HRE DNA with various G4C2 repeats. They exhibited diverse G-quadruplex folds in potassium ions. Furthermore, we determined the topology of a G-quadruplex formed by d(G4C2)(4). It favors a monomeric fold and forms a chair-type G-quadruplex with a four-layer antiparallel G-tetra core and three edgewise loops, which is distinct from known structures of chair-type G-quadruplexes. Our findings highlight the conformational heterogeneity of C9orf72 HRE DNA, and may lay the necessary structural basis for designing small molecules for the modulation of ALS/FTD pathogenesis.